Dendrimer nanoplatforms for veterinary medicine applications: A concise overview. Issue 5 (May 2022) - Mignani, Serge; Shi, Xiangyang; Rodrigues, João; Tomás, Helena; Majoral, Jean-Pierre
Graphical abstract: Highlights: The sick animal is indeed a threat to man. Dendrimer nanoplatforms can be used for veterinary medicine applications. Foot and mouth disease, swine fever, HCA, rabies, and H9N2 avian influenza virus. Intramuscular, subcutaneous, intravenous, and intraperitoneal routes of administrations are used. Abstract : Within the nanoparticle (NP) space, dendrimers are becoming increasingly important in the field of nanomedicine, not only to treat human diseases, but also in veterinary medicine, which represents a new therapeutic approach. Major applications include using dendrimers to tackle highly contagious foot-and-mouth disease virus (FMDV) and swine fever virus (SFV) in pigs, FMDV in cattle, hypothermic circulatory arrest (HCA) in dogs, rabies, and H9N2 avian influenza virus in chickens. As we review here, intramuscular (im) subcutaneous (sc), intravenous (iv), and intraperitoneal (ip) routes of administration can be used for the successful application of dendrimers in animals.